Intensi Mahasiswa Dalam Berwirausaha - R. Agrosamdhyo (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
The mindset as a Job Seeker and not as a Job Creature after completing college is a problem that must be solved by all parties, both the government, educational institutions, the business world, and the community. One of them is planning a business as an individual business career choice in the future after graduating from college. This study aims to map the intentions of students majoring in Islamic Economics at STAI Denpasar in entrepreneurship so that its development can be accepted in society. The population in this study were STAI Denpasar students. The research was conducted using qualitative techniques, with the purposive sampling method as a sampling method. The results of the research are STAI Denpasar students have negative intentions in starting a business. Negative means that there are still many students who think that it is very difficult to open their own business. To become successful entrepreneurs, intentions must also be supported by concrete actions, the real actions they take are sure to start a business, learn from entrepreneurs who have been successful and dare to start a business with existing limitations.